THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENGLISH LANGUAGE TEACHING: OPPORTUNITIES, CHALLENGES, AND FUTURE PERSPECTIVES - O’rozaliyeva Husniya Azimjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Artificial Intelligence (AI) has emerged as a transformative technology in modern education, significantly influencing the teaching and learning of foreign languages. In English Language Teaching (ELT), AI-powered tools such as intelligent tutoring systems, chatbots, speech recognition software, and adaptive learning platforms have introduced innovative approaches to language instruction. These technologies offer personalized learning experiences, immediate feedback, enhanced learner engagement, and greater accessibility to educational resources. However, the integration of AI in ELT also presents challenges, including concerns regarding academic integrity, data privacy, technological dependence, and the reduction of human interaction in language learning environments. This theoretical review examines the role of AI in English language teaching through an analysis of recent scholarly literature. The study explores both the advantages and limitations of AI applications in ELT and discusses their implications for teachers, learners, and educational institutions. The findings indicate that AI has the potential to improve language acquisition and teaching effectiveness; however, its successful implementation requires a balanced approach that combines technological innovation with pedagogical principles and human-centered instruction.